Twinning in-situ self-grown particle synergistically reinforced magnesium-based composite filler material, and preparation method and application thereof

CN118081178BActive Publication Date: 2026-10-09TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410456117.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-16
Publication Date
2026-10-09
Estimated Expiration
2044-04-16

AI Technical Summary

Technical Problem

但增强相与钎料难以润湿形成有效的冶金结合,导致增强相与钎料界面容易萌生裂纹,降低钎焊接头的强度

Benefits of technology

[0020] The chemical composition of the synergistic in-situ self-generated particles of the present invention is Mg-Zn-Al-Y, wherein the amount of Zn added is 44-46 wt.%, and the composition of the solder is close to the Mg-Zn eutectic composition, which can significantly reduce the melting point of the solder and improve its fluidity; the amount of Al added is 0.6-1 wt.%, which can improve the strength of the solder and the strength of the brazed joint through solid solution strengthening; the amount of Y added is 0.1-1 wt.%, which can improve the fluidity of the solder, improve the wettability between the solder and the base material, and can also generate Zn-Y-Al particles and MgZn2 particles in situ with Zn and Al, refine the grain size, and further improve the strength of the brazed joint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118081178B_ABST
    Figure CN118081178B_ABST
Patent Text Reader

Abstract

The application relates to a twin in-situ self-grown particle synergistically reinforced magnesium-based composite brazing filler metal and a preparation method and application thereof, and relates to a reinforced magnesium-based composite brazing filler metal and a preparation method and application thereof. The application aims to solve the technical problem that it is difficult to form an effective joint by magnesium alloy brazing at present. In the application, Al and Y are introduced into a magnesium-zinc-based brazing filler metal, a step-variable-temperature diffusion + multi-stage frequency division ultrasonic in-situ self-grown casting process is adopted, Zn-Al-Y and MgZn2 reinforced particles are in-situ self-grown, and a novel twin in-situ self-grown particle synergistically reinforced magnesium-based composite brazing filler metal with excellent brazing performance is prepared. The composite brazing filler metal provided by the application has the advantages of low brazing temperature, small influence on a base material and high joint shear strength when brazing Mg-Zn magnesium alloys, and can be used in brazing processes such as furnace brazing, high-frequency induction brazing, protective atmosphere brazing and ultrasonic wave assisted brazing, and has a wide application prospect in precise connection of Mg-Zn magnesium alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a reinforced magnesium-based composite solder, its preparation method, and its application. Background Technology

[0002] Magnesium alloys possess advantages such as low density, high specific strength, high specific stiffness, and good electromagnetic shielding performance, making them widely applicable in aerospace, electronics, and defense industries. They are currently one of the most important lightweight structural materials. The widespread application of magnesium alloys necessitates the development of reliable connections, requiring the development of brazing filler metals for magnesium alloy brazing. To improve the brazed joint microstructure and strength, one approach is to add reinforcing phase particles, such as SiC and Ti particles, during filler metal preparation. This reduces residual stress in the filler metal and improves the reliability of the brazed joint. However, the reinforcing phase and filler metal are difficult to wet and form an effective metallurgical bond, leading to easy crack initiation at the interface and reducing the strength of the brazed joint. Furthermore, several other issues need to be addressed, such as the high melting point of the filler metal, resulting in high brazing temperatures that severely degrade the properties of the base material; the presence of expensive metals in the filler metal, increasing costs and hindering commercial application; and the presence of metals harmful to human health in the filler metal. Currently, research on brazing filler metals for magnesium alloys is insufficient. Therefore, there is an urgent need to develop a brazing filler metal that meets the requirements of magnesium alloy brazing applications, has a simple preparation process, uniform composition and structure, minimal impact on the properties of the base material, low alloy cost, is harmless to the human body, and has good mechanical properties of the brazed joint. Summary of the Invention

[0003] The present invention aims to solve the technical problem that it is difficult to form an effective joint in the current brazing of magnesium alloys, and provides a magnesium-based composite brazing filler metal with synergistic reinforcement of twin-generated in-situ self-generated particles, its preparation method and application.

[0004] The mass percentage of each element in the synergistic reinforcement magnesium-based composite brazing filler metal of the present invention is as follows: Zn: 44%–46%, Al: 0.6%–1%, Y: 0.1%–1%, with the balance being Mg.

[0005] The preparation method of the magnesium-based composite solder with synergistic reinforcement of twin-generated in-situ self-generated particles of the present invention is as follows:

[0006] S1. Pretreatment of raw materials: The surface oxide layer of pure magnesium ingots, pure zinc ingots, pure aluminum ingots, and Mg-Y master alloy is removed by grinding. Then, the four raw materials are weighed according to the following mass percentage of each element and dried:

[0007] Zn: 44%–46%, Al: 0.6%–1%, Y: 0.1%–1%, balance Mg;

[0008] S2, stepwise temperature-dependent diffusion:

[0009] Step 1: Heat the crucible to 780℃~790℃ and then put in the pure magnesium ingot weighed in Step 1;

[0010] The second step involves melting pure magnesium ingots and then cooling them to 690℃~720℃. Pure zinc and pure aluminum ingots weighed in step one are then added, followed by the first stage of heat preservation and diffusion treatment. The first stage heat preservation and diffusion treatment process is as follows: first, heat preservation for 10min~15min, then starting the stirring paddle and stirring counterclockwise for 6min~9min at a speed of 10r / min~20r / min; then stirring clockwise for 11min~14min at a speed of 10r / min~20r / min.

[0011] The third step is to heat the melt to 760℃~780℃, add the Mg-Y master alloy weighed in step one, and perform a second stage of heat preservation and diffusion treatment to obtain an in-situ self-generated composite melt.

[0012] The second stage of heat preservation and diffusion treatment process is as follows: first, heat preservation for 5 min to 10 min, then start the agitator to stir counterclockwise for 6 min to 9 min at a stirring speed of 20 r / min to 30 r / min; then stir clockwise for 11 min to 14 min at a stirring speed of 20 r / min to 30 r / min.

[0013] Throughout the entire process of S2, protective gas is continuously introduced;

[0014] S3. Multi-stage frequency division ultrasonic in-situ self-generating process: The preheated ultrasonic rod is placed 3cm to 5cm below the surface of the in-situ self-generated composite melt obtained in S2, and then multi-stage frequency division ultrasound is performed. The specific process is as follows:

[0015] First stage: Cool the in-situ self-generated composite melt to 650℃~720℃, and sonicate it for 5min~8min under the conditions of ultrasonic power and ultrasonic frequency of 1200W~1500W and 30kHz~40kHz respectively.

[0016] Second stage: Cool the in-situ self-generated composite melt to 520℃~580℃, and sonicate it for 8min~12min under ultrasonic power and ultrasonic frequency of 1800W~2200W and 50kHz~60kHz respectively.

[0017] The third stage: Cooling the in-situ self-generated composite melt to 450℃~500℃ under ultrasonic power and ultrasonic frequency conditions of 1800W~2200W and 20kHz~30kHz respectively.

[0018] S4. Casting and molding: Preheat the mold to 170℃~200℃; after S3 is completed, pour the in-situ self-generated composite melt into the mold, and after natural cooling and solidification, obtain the twin-generated in-situ self-generated particle synergistic reinforced magnesium-based composite brazing filler metal.

[0019] The twin-generated in-situ self-generated particles synergistically reinforced magnesium-based composite brazing filler metal of the present invention is used for brazing two identical base materials Mg-Zn magnesium alloys, with a brazing temperature of 370℃~500℃ and a filler metal thickness of 0.3mm~1.2mm.

[0020] The chemical composition of the synergistic in-situ self-generated particles of the present invention is Mg-Zn-Al-Y, wherein the amount of Zn added is 44-46 wt.%, and the composition of the solder is close to the Mg-Zn eutectic composition, which can significantly reduce the melting point of the solder and improve its fluidity; the amount of Al added is 0.6-1 wt.%, which can improve the strength of the solder and the strength of the brazed joint through solid solution strengthening; the amount of Y added is 0.1-1 wt.%, which can improve the fluidity of the solder, improve the wettability between the solder and the base material, and can also generate Zn-Y-Al particles and MgZn2 particles in situ with Zn and Al, refine the grain size, and further improve the strength of the brazed joint.

[0021] This invention can control the number of twin in-situ self-generated particles by controlling the ratio and amount of Al and Y; the step-by-step temperature diffusion + multi-stage frequency ultrasonic in-situ self-generated casting process can reduce casting defects in the brazing filler metal, refine the size of the in-situ self-generated particles, avoid agglomeration, and achieve control over the size and distribution of twin in-situ self-generated particles in the brazing filler metal.

[0022] The present invention relates to a synergistic in-situ self-generated particle-reinforced magnesium-based composite brazing filler metal with a melting temperature range of 340℃ to 355℃ and a melting range of 5℃ to 16℃. It is suitable for brazing Mg-Zn magnesium alloys with brazing temperatures of 370℃ to 500℃ and solidus lines above 500℃. At the brazing temperature, when two Mg-5Zn-1Gd-1Y magnesium alloys are joined using transient liquid phase diffusion brazing (TLP), the brazed joint is free of defects such as porosity and slag inclusions, and the room temperature shear strength of the brazed joint can reach 30MPa to 50MPa.

[0023] The twin-generated in-situ self-generated particles synergistically reinforced magnesium-based composite brazing filler metal provided by this invention has the advantages of low brazing temperature, minimal impact on the base material, and high joint shear strength when brazing Mg-Zn magnesium alloys. It can be used in brazing processes such as furnace brazing, high-frequency induction brazing, protective atmosphere brazing, and ultrasonic-assisted brazing, and has broad application prospects in the precision joining of Mg-Zn magnesium alloys. Attached Figure Description

[0024] Figure 1SEM image of the magnesium-based composite brazing filler metal with synergistic reinforcement of twin-generated in-situ self-generated particles prepared in Experiment 3;

[0025] Figure 2 SEM image of the brazed joint after brazing with the filler metal from Experiment 3;

[0026] Figure 3 for Figure 1 Energy dispersive X-ray spectroscopy (EDS) plot of phase 44 at midpoint;

[0027] Figure 4 for Figure 1 Energy dispersive X-ray spectroscopy (EDS) plot of the phase at midpoint 45°.

[0028] Figure 5 for Figure 1 Energy dispersive X-ray spectroscopy (EDS) plot of phase 46 at midpoint;

[0029] Figure 6 for Figure 1 Energy dispersive spectroscopy (EDS) plot of phase at midpoint 54. Detailed Implementation

[0030] Specific Implementation Method 1: This implementation method is a magnesium-based composite brazing filler metal with synergistic reinforcement of twin-generated in-situ self-generated particles, wherein the mass percentage of each element is: Zn: 44%~46%, Al: 0.6%~1%, Y: 0.1%~1%, and the balance is Mg.

[0031] Specific Implementation Method Two: This implementation method is the preparation method of the magnesium-based composite brazing filler metal with synergistic reinforcement of twin-generated in-situ self-generated particles in Specific Implementation Method One. The specific process is as follows:

[0032] S1. Pretreatment of raw materials: The surface oxide layer of pure magnesium ingots, pure zinc ingots, pure aluminum ingots, and Mg-Y master alloy is removed by grinding. Then, the four raw materials are weighed according to the following mass percentage of each element and dried:

[0033] Zn: 44%–46%, Al: 0.6%–1%, Y: 0.1%–1%, balance Mg;

[0034] S2, stepwise temperature-dependent diffusion:

[0035] Step 1: Heat the crucible to 780℃~790℃ and then put in the pure magnesium ingot weighed in Step 1;

[0036] The second step involves melting pure magnesium ingots and then cooling them to 690℃~720℃. Pure zinc and pure aluminum ingots weighed in step one are then added, followed by the first stage of heat preservation and diffusion treatment. The first stage heat preservation and diffusion treatment process is as follows: first, heat preservation for 10min~15min, then starting the stirring paddle and stirring counterclockwise for 6min~9min at a speed of 10r / min~20r / min; then stirring clockwise for 11min~14min at a speed of 10r / min~20r / min.

[0037] The third step is to heat the melt to 760℃~780℃, add the Mg-Y master alloy weighed in step one, and perform a second stage of heat preservation and diffusion treatment to obtain an in-situ self-generated composite melt.

[0038] The second stage of heat preservation and diffusion treatment process is as follows: first, heat preservation for 5 min to 10 min, then start the agitator to stir counterclockwise for 6 min to 9 min at a stirring speed of 20 r / min to 30 r / min; then stir clockwise for 11 min to 14 min at a stirring speed of 20 r / min to 30 r / min.

[0039] Throughout the entire process of S2, protective gas is continuously introduced;

[0040] S3. Multi-stage frequency division ultrasonic in-situ self-generating process: The preheated ultrasonic rod is placed 3cm to 5cm below the surface of the in-situ self-generated composite melt obtained in S2, and then multi-stage frequency division ultrasound is performed. The specific process is as follows:

[0041] First stage: Cool the in-situ self-generated composite melt to 650℃~720℃, and sonicate it for 5min~8min under the conditions of ultrasonic power and ultrasonic frequency of 1200W~1500W and 30kHz~40kHz respectively.

[0042] Second stage: Cool the in-situ self-generated composite melt to 520℃~580℃, and sonicate it for 8min~12min under ultrasonic power and ultrasonic frequency of 1800W~2200W and 50kHz~60kHz respectively.

[0043] The third stage: Cooling the in-situ self-generated composite melt to 450℃~500℃ under ultrasonic power and ultrasonic frequency conditions of 1800W~2200W and 20kHz~30kHz respectively.

[0044] S4. Casting and molding: Preheat the mold to 170℃~200℃; after S3 is completed, pour the in-situ self-generated composite melt into the mold, and after natural cooling and solidification, obtain the twin-generated in-situ self-generated particle synergistic reinforced magnesium-based composite brazing filler metal.

[0045] Specific Implementation Method 3: This implementation method differs from Specific Implementation Method 2 in that the Mg-Y master alloy mentioned in S1 is Mg-30Y. Everything else is the same as in Specific Implementation Method 2.

[0046] Specific Implementation Method Four: This implementation method differs from Specific Implementation Method Two in that the protective gas mentioned in S2 is a mixture of CO2 and SF6, wherein the volume fraction of SF6 is 3% to 5%. Everything else is the same as in Specific Implementation Method Two.

[0047] Specific Implementation Method Five: This implementation method differs from Specific Implementation Method Two in that the preheating temperature of the ultrasonic rod in S3 is 680℃. Everything else is the same as in Specific Implementation Method Two.

[0048] Specific Implementation Method Six: This implementation method is the application of the twin-generated in-situ self-generated particles synergistically reinforced magnesium-based composite brazing filler metal prepared in Specific Implementation Method Two. Specifically, the twin-generated in-situ self-generated particles synergistically reinforced magnesium-based composite brazing filler metal is applied to brazing two identical base materials Mg-Zn magnesium alloys. The brazing temperature is 370℃~500℃, and the thickness of the brazing filler metal is 0.3mm~1.2mm.

[0049] The invention was verified using the following experiments:

[0050] Experiment 1: This experiment demonstrates a method for preparing a magnesium-based composite solder with synergistic reinforcement from twin-generated in-situ self-generated particles. The specific process is as follows:

[0051] S1. Pretreatment of raw materials: The surface oxide layer of pure magnesium ingots, pure zinc ingots, pure aluminum ingots, and Mg-Y master alloy is removed by grinding. Then, the four raw materials are weighed according to the following mass percentage of each element and dried:

[0052] Zn: 44%, Al: 0.6%, Y: 0.25%, balance Mg;

[0053] The Mg-Y master alloy is Mg-30Y;

[0054] S2, stepwise temperature-dependent diffusion:

[0055] Step 1: Heat the crucible to 780°C and then place the pure magnesium ingot weighed in Step 1 into it;

[0056] The second step involves melting pure magnesium ingots and then cooling them to 690°C. Pure zinc and pure aluminum ingots weighed in step one are then added, and the first stage of heat preservation and diffusion treatment is carried out. The first stage of heat preservation and diffusion treatment is as follows: heat preservation for 10 minutes, then start stirring in a counterclockwise direction for 6 minutes at a stirring speed of 10 r / min; then stir in a clockwise direction for 14 minutes at a stirring speed of 10 r / min.

[0057] The third step is to heat the melt to 760°C, add the Mg-Y master alloy weighed in the first step, and perform a second stage of heat preservation and diffusion treatment to obtain an in-situ self-generated composite melt.

[0058] The second stage of heat preservation and diffusion treatment process is as follows: first, heat preservation for 5 minutes, then start the agitator to stir counterclockwise for 6 minutes at a stirring speed of 20 r / min; then stir clockwise for 14 minutes at a stirring speed of 20 r / min.

[0059] Throughout the S2 process, a protective gas is continuously introduced. The protective gas is a mixture of CO2 and SF6, with SF6 having a volume fraction of 3%.

[0060] S3. Multi-stage frequency division ultrasonic in-situ self-generating process: The preheated ultrasonic rod (680℃) is placed 3cm below the surface of the in-situ self-generated composite melt obtained in S2, and then multi-stage frequency division ultrasonication is performed. The specific process is as follows:

[0061] First stage: Cool the in-situ self-generated composite melt to 650℃ and sonicate it for 5 minutes under ultrasonic power and ultrasonic frequency of 1200W and 30kHz respectively.

[0062] Second stage: Cool the in-situ self-generated composite melt to 520℃ and sonicate it for 8 minutes under ultrasonic power and ultrasonic frequency of 1800W and 50kHz respectively.

[0063] The third stage: Cooling the in-situ self-generated composite melt to 450℃ under ultrasonic power and ultrasonic frequency of 1800W and 20kHz respectively.

[0064] S4. Casting and molding: Preheat the mold to 170℃; after S3 is completed, pour the in-situ self-generated composite melt into the mold, and after natural cooling and solidification, obtain the twin-generated in-situ self-generated particle synergistic reinforced magnesium-based composite brazing filler metal.

[0065] Experiment 2: This experiment demonstrates a method for preparing a magnesium-based composite solder with synergistic reinforcement from twin-generated in-situ self-generated particles. The specific process is as follows:

[0066] S1. Pretreatment of raw materials: The surface oxide layer of pure magnesium ingots, pure zinc ingots, pure aluminum ingots, and Mg-Y master alloy is removed by grinding. Then, the four raw materials are weighed according to the following mass percentage of each element and dried:

[0067] Zn: 45%, Al: 0.8%, Y: 0.5%, balance Mg;

[0068] The Mg-Y master alloy is Mg-30Y;

[0069] S2, stepwise temperature-dependent diffusion:

[0070] Step 1: Heat the crucible to 780°C and then place the pure magnesium ingot weighed in Step 1 into it;

[0071] The second step involves melting the pure magnesium ingots and then cooling them to 700°C. The pure zinc and pure aluminum ingots weighed in step one are then added, and the first stage of heat preservation and diffusion treatment is performed. The first stage heat preservation and diffusion treatment process is as follows: heat preservation for 10 minutes, then starting the stirring paddle to stir counterclockwise for 8 minutes at a stirring speed of 15 r / min; then stirring clockwise for 12 minutes at a stirring speed of 15 r / min.

[0072] The third step is to heat the melt to 770°C, add the Mg-Y master alloy weighed in the first step, and perform a second stage of heat preservation and diffusion treatment to obtain an in-situ self-generated composite melt.

[0073] The second stage of heat preservation and diffusion treatment process is as follows: first, heat preservation for 5 minutes, then start the agitator to stir counterclockwise for 8 minutes at a stirring speed of 25 r / min; then stir clockwise for 12 minutes at a stirring speed of 25 r / min.

[0074] Throughout the S2 process, a protective gas is continuously introduced. The protective gas is a mixture of CO2 and SF6, with SF6 having a volume fraction of 3%.

[0075] S3. Multi-stage frequency division ultrasonic in-situ self-generating process: The preheated ultrasonic rod (680℃) is placed 4cm below the surface of the in-situ self-generated composite melt obtained in S2, and then multi-stage frequency division ultrasonication is performed. The specific process is as follows:

[0076] First stage: Cool the in-situ self-generated composite melt to 680℃ and sonicate it for 6 minutes under ultrasonic power and ultrasonic frequency of 1300W and 35kHz respectively.

[0077] Second stage: Cool the in-situ self-generated composite melt to 550℃ and sonicate it for 10 minutes under ultrasonic power and ultrasonic frequency of 2000W and 55kHz respectively.

[0078] The third stage: Cooling the in-situ self-generated composite melt to 480℃ under ultrasonic power and ultrasonic frequency of 2000W and 25kHz respectively.

[0079] S4. Casting and molding: Preheat the mold to 180℃; after S3 is completed, pour the in-situ self-generated composite melt into the mold, and after natural cooling and solidification, obtain the twin-generated in-situ self-generated particle synergistic reinforced magnesium-based composite brazing filler metal.

[0080] Experiment 3: This experiment demonstrates a method for preparing a magnesium-based composite solder with synergistic reinforcement from twin-generated in-situ self-generated particles. The specific process is as follows:

[0081] S1. Pretreatment of raw materials: The surface oxide layer of pure magnesium ingots, pure zinc ingots, pure aluminum ingots, and Mg-Y master alloy is removed by grinding. Then, the four raw materials are weighed according to the following mass percentage of each element and dried:

[0082] Zn: 46%, Al: 1%, Y: 1%, balance Mg;

[0083] The Mg-Y master alloy is Mg-30Y;

[0084] S2, stepwise temperature-dependent diffusion:

[0085] Step 1: Heat the crucible to 780°C and then place the pure magnesium ingot weighed in Step 1 into it;

[0086] The second step involves melting the pure magnesium ingots and then cooling them to 720°C. The pure zinc and pure aluminum ingots weighed in step one are then added, and the first stage of heat preservation and diffusion treatment is performed. The first stage heat preservation and diffusion treatment process is as follows: heat preservation for 10 minutes, then starting the stirring paddle to stir counterclockwise for 9 minutes at a stirring speed of 20 r / min; then stirring clockwise for 11 minutes at a stirring speed of 20 r / min.

[0087] The third step is to heat the melt to 780°C, add the Mg-Y master alloy weighed in the first step, and perform a second stage of heat preservation and diffusion treatment to obtain an in-situ self-generated composite melt.

[0088] The second stage of heat preservation and diffusion treatment process is as follows: first, heat preservation for 5 minutes, then start the agitator to stir counterclockwise for 9 minutes at a stirring speed of 30 r / min; then stir clockwise for 11 minutes at a stirring speed of 30 r / min.

[0089] Throughout the S2 process, a protective gas is continuously introduced. The protective gas is a mixture of CO2 and SF6, with the volume fraction of SF6 being 4%.

[0090] S3. Multi-stage frequency division ultrasonic in-situ self-generating process: The preheated ultrasonic rod (680℃) is placed 5cm below the surface of the in-situ self-generated composite melt obtained in S2, and then multi-stage frequency division ultrasonication is performed. The specific process is as follows:

[0091] First stage: Cool the in-situ self-generated composite melt to 720℃ and sonicate it for 8 minutes under ultrasonic power and ultrasonic frequency of 1500W and 40kHz respectively.

[0092] Second stage: Cool the in-situ self-generated composite melt to 580℃ and sonicate it for 12 minutes under ultrasonic power and ultrasonic frequency of 2200W and 60kHz respectively.

[0093] The third stage: Cooling the in-situ self-generated composite melt to 500℃ under ultrasonic power and ultrasonic frequency of 2200W and 30kHz respectively.

[0094] S4. Casting and molding: Preheat the mold to 200℃; after S3 is completed, pour the in-situ self-generated composite melt into the mold, and after natural cooling and solidification, obtain the twin-generated in-situ self-generated particle synergistic reinforced magnesium-based composite brazing filler metal.

[0095] Comparative Example: This comparative example is a magnesium-based solder. No Al or Y elements were added to the solder. The Zn element accounted for 45% of the solder by mass, with the balance being Mg. The solder preparation method is as follows:

[0096] S1. Pretreatment of raw materials: Grind the pure magnesium ingots and pure zinc ingots to remove the surface oxide layer, then weigh the two raw materials according to the above element ratio and dry them:

[0097] S2, stepwise temperature-dependent diffusion:

[0098] Step 1: Heat the crucible to 780°C and then place the pure magnesium ingot weighed in Step 1 into it;

[0099] The second step involves melting the pure magnesium ingot and cooling it to 720°C. Then, the pure zinc ingot weighed in step one is added, and the first stage of heat preservation and diffusion treatment is carried out. The first stage heat preservation and diffusion treatment process is as follows: heat preservation for 10 minutes, then start the stirring paddle to stir counterclockwise for 9 minutes at a stirring speed of 20 r / min; then stir clockwise for 11 minutes at a stirring speed of 20 r / min.

[0100] The third step is to cool the melt to 500°C.

[0101] Throughout the S2 process, a protective gas is continuously introduced. The protective gas is a mixture of CO2 and SF6, with the volume fraction of SF6 being 4%.

[0102] S3, Casting: Preheat the mold to 200℃; after S2 is completed, pour the melt into the mold and let it cool and solidify naturally to obtain magnesium-based brazing filler metal.

[0103] Instantaneous liquid phase diffusion brazing (TLP) was performed on two base materials, Mg-5Zn-1Gd-1Y magnesium alloy, using the brazing filler metals prepared in Experiments 1 to 3 and the comparative example. The dimensions of the base material were 30mm × 30mm × 3mm, and the dimensions of the brazing filler metal were 30mm × 30mm × 0.8mm. The brazing temperature was 450℃, the holding time was 20min, and the bonding pressure was 2MPa. The shear strength results of the brazed joints are shown in Table 1.

[0104] Table 1

[0105]

[0106] Figure 1 The image shows a SEM image of the magnesium-based composite brazing filler metal prepared in Experiment 3, which is synergistically reinforced with in-situ self-generated particles. The image indicates that the filler metal is of good quality, with no obvious impurities or defects. Numerous in-situ self-generated Zn-Y-Al particles and MgZn2 particles are dispersed within the magnesium alloy matrix, resulting in a uniform microstructure.

[0107] Figure 2 The SEM images of the brazed joint after brazing with the filler metal from Experiment 3 are shown in Table 1. The images reveal no defects such as inclusions or pores in the brazed joint, indicating good bonding between the filler metal and the base material. The brazed joint width is approximately 10 μm. Numerous dispersed in-situ self-generated Zn-Y-Al and MgZn2 particles are present in the brazed joint, alleviating stress concentration and enhancing the shear strength of the brazed joint through second-phase strengthening.

[0108] Figure 3 for Figure 1 The energy dispersive spectroscopy (EDS) plot of phase 44 shows that it is a Zn-Y-Al particle. Figure 4 for Figure 1 The energy dispersive spectroscopy (EDS) pattern of the phase at midpoint 45 shows that the gray matrix is ​​a MgZn eutectic structure. Figure 5 for Figure 1 The energy dispersive spectroscopy (EDS) plot of phase 46 shows that it is MgZn2 particles. Figure 6 for Figure 1 The energy dispersive spectroscopy (EDS) plot of phase 54 shows that it is an α-Mg solid solution.

[0109] The magnesium-based composite brazing filler metal with synergistic reinforcement by twin in-situ self-generated particles in this invention has a uniform composition and structure, a simple preparation process, and high shear performance of the brazed joint, and has broad application prospects in the brazing of rare earth magnesium alloys.

Claims

1. A method for preparing a magnesium-based composite solder with synergistic reinforcement from twin-generated in-situ self-generated particles, characterized in that... The preparation method of the magnesium-based composite solder with synergistic reinforcement of twin in-situ self-generated particles is as follows: S1. Pretreatment of raw materials: The surface oxide layer of pure magnesium ingots, pure zinc ingots, pure aluminum ingots, and Mg-Y master alloy is removed by grinding. Then, the four raw materials are weighed according to the following mass percentage of each element and dried: Zn: 44%~46%, Al: 0.6%~1%, Y: 0.1%~1%, balance Mg; S2, stepwise temperature-dependent diffusion: Step 1: Heat the crucible to 780℃~790℃ and then put in the pure magnesium ingot weighed in S1; The second step involves melting pure magnesium ingots and then cooling them to 690℃~720℃. Pure zinc and pure aluminum ingots weighed out (S1) are added, followed by the first stage of heat preservation and diffusion treatment. The first stage heat preservation and diffusion treatment process is as follows: heat preservation for 10-15 minutes, then starting the stirring paddle and stirring counterclockwise for 6-9 minutes at a speed of 10-20 r / min; then stirring clockwise for 11-14 minutes at a speed of 10-20 r / min. The third step is to heat the melt to 760℃~780℃, add the Mg-Y master alloy weighed in S1 and perform a second stage of heat preservation and diffusion treatment to obtain an in-situ self-generated composite melt. The second stage of heat preservation and diffusion treatment process is as follows: first, heat preservation for 5 min to 10 min, then start the agitator to stir counterclockwise for 6 min to 9 min at a stirring speed of 20 r / min to 30 r / min; then stir clockwise for 11 min to 14 min at a stirring speed of 20 r / min to 30 r / min. Throughout the entire process of S2, protective gas is continuously introduced; S3. Multi-stage frequency division ultrasonic in-situ self-generated process: The preheated ultrasonic rod is placed 3cm to 5cm below the surface of the in-situ self-generated composite melt obtained in S2, and then multi-stage frequency division ultrasonication is performed. The specific process is as follows: First stage: Cool the in-situ self-generated composite melt to 650℃~720℃, and sonicate it for 5min~8min under ultrasonic power and ultrasonic frequency of 1200W~1500W and 30kHz~40kHz respectively. Second stage: Cool the in-situ self-generated composite melt to 520℃~580℃, and sonicate it for 8min~12min under ultrasonic power and ultrasonic frequency of 1800W~2200W and 50kHz~60kHz respectively. Level 3: Cool the in-situ self-generated composite melt to 450℃~500℃ under ultrasonic power and ultrasonic frequency conditions of 1800W~2200W and 20kHz~30kHz respectively. S4. Casting and molding: Preheat the mold to 170℃~200℃; after S3 is completed, pour the in-situ self-generated composite melt into the mold, and after natural cooling and solidification, obtain the twin-generated in-situ self-generated particle synergistic reinforced magnesium-based composite brazing filler metal.

2. The method for preparing a magnesium-based composite solder with synergistic reinforcement from twin-generated in-situ self-generated particles according to claim 1, characterized in that... The Mg-Y master alloy mentioned in S1 is Mg-30Y.

3. The preparation method of a magnesium-based composite brazing filler metal with synergistic reinforcement of twin-generated in-situ self-generated particles according to claim 1, characterized in that the protective gas in S2 is a mixture of CO2 and SF6, wherein the volume fraction of SF6 is 3%~5%.

4. The preparation method of a magnesium-based composite solder with synergistic reinforcement of twin-generated in-situ self-generated particles according to claim 1, characterized in that... The preheating temperature of the ultrasonic rod in S3 is 680℃.

Citation Information

Patent Citations

  • Magnesium alloy middle temperature brazing material

    CN101323060A

  • Brazing filler metal for brazing Al-Mg-Zn magnesium alloy

    CN102069316A